(untitled) (Journal of Human Sciences, 2021)
This research discusses the role of Arabic poetry in strengthening the educational values advocated by modern educational curricula and whose implementation has been assigned to the faculties of education. Its impact was clear and evident in human studies, and that impact was absent in applied sciences as a result of the lack of many of the implementers of its educational programs in these departments to the qualified competence for how to practice these values through their curricula. The study shed light on the educational values in which the faculties of education are interested and seek to inculcate in their members, to achieve the goals set for their outputs to build the individual and society, and how this is implemented in all the scientific departments of the faculties of education. This study started from the central problematic question, namely, how does poetry contribute to the consolidation of educational values in the students of the Arabic language department in the faculties of education? And how are they directed to study topics which carry those values for research? The study adopted the descriptive-analytical approach in describing and analysing the phenomenon, and the study was divided into two parts, one theoretical and the other practical, focusing on examples of those values that our Arab poetry invoked since the pre-Islamic era by some of its poets.